Effects of an 8-week pre-seasonal training on the aerobic fitness of professional soccer players - Michaelides, M. A.; Parpa, K. M.; Zacharia, A. I. (The Journal of Strength and Conditioning Research, 2021)
Pre-season in soccer training develops the physical requisites for competition and usually consists of a high volume of aerobic and anaerobic conditioning training including friendly games. The purpose of the study was to determine the effects of pre-season training on the aerobic fitness of professional soccer players. Nineteen professional male soccer players (age = 27.37 ± 3.67 years, height = 179.61 ± 5.17 cm, and body fat percentage = 11.3 ± 3.19%) participated in this study performed an incremental cardiopulmonary exercise testing on a treadmill before and after the 8 weeks of pre-season preparation. The results were analyzed using paired t tests, revealing significant differences on several indices. The subjects improved significantly on maximal aerobic capacity (Vo2max) and lasted significantly longer on the treadmill (p < 0.05). The Vo2 at ventilatory threshold (VT) and respiratory compensation point (RCP) increased significantly (p < 0.05). The running velocity at ventilatory thresholds (vVT and vRCP) and at Vo2 max (vVo2max) also increased significantly (p < 0.05). In conclusion, the results of this study, as expected, demonstrated that the proposed 8 weeks of pre-season training program was sufficient to cause significant improvements on the aerobic performance indices of professional soccer players. The study confirms the beneficial changes in the process of adaptations that occur with this type of training and can assist coaches and trainers in planning a successful pre-season training program.